INVESTIGATION OF THE CLINICAL FACTOR ASSOCIATED WITH INTRADIALYTIC HYPOTENSION: INSIGHT FROM KIDS REGISTRY. (April 2021) - Tokushige, Akihiro; Ikeda, Yoshiyuki; Kanda, Daisuke; Sonoda, Takeshi; Yoshikawa, Akiko; Imamura, Masakazu; Ohishi, Mitsuru
Abstract : Objective: Intradialytic hypotension (IDH) is a major complication during hemodialysis (HD)session, associated with increased risk of cardiovascular events and mortality. Its pathophysiology is believed to be multifactorial and remains not well elucidated. The aim of this study is to investigate the clinical factor associated with IDH. Design and method: The KIDS Registry is a prospective cohort study in patients with maintenance dialysis at 4 facilities in Kagoshima Prefecture in Japan were consecutively enrolled (531 patients) June 2015 to the present. 345 patients who were finished over 1-year follow-up and available blood pressure data during HD were made to be an analysis subject, and divided into two groups according to the severity of decrease in systolic blood pressure (SBP) during HD; hypotension (IDH group, n = 148) and non-hypotension (non-IDH group, n = 197) groups showing an SBP decrease during HD of 20 mmHg or more, and less than 20 mmHg, respectively, compared with the SBP value before HD. Results: Prior peripheral vascular disease (PVD), history of diabetes mellitus (DM), history of hypertension and pre-urea nitrogen value were significantly higher in hypotension group than in non-hypotension group. We performed multivariate logistic regression to test for the independent contribution to IDH. Prior PVD(Odds Ratio (OR): 1.77, 95% Confidence Interval (CI): 1.01 to 3.09), history of DM (OR: 2.34, 95%CI: 1.39 to 3.93), and pre-urea nitrogen value (OR: 1.03, 95%CI: 1.01 to 1.05) were independent associating factors to IDH after adjusted by several clinical relevant factors. Conclusions: Atherosclerotic disease such as PVD and DM which was the important disease leading to atherosclerosis were significant associating factors with IDH. IDH may be associated with atherosclerosis in HD patients.